2018
DOI: 10.31351/vol27iss2pp123-134
|View full text |Cite
|
Sign up to set email alerts
|

Novel Combination for Self-Nanoemulsifying Drug Delivery System of Candesartan Cilexetil

Abstract: Solubility problem of many of effective pharmaceutical molecules are still one of the major obstacle in theformulation of such molecules. Candesartan cilexetil (CC) is angiotensin II receptor antagonist with very low water solubility and this result in low and variable bioavailability. Self- emulsifying drug delivery system (SEDDS) showed promising result in overcoming solubility problem of many drug molecules. CC was prepared as SEDDS by using novel combination of two surfactants (tween 80 and cremophore EL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…All the prepared liquid SEDD formulas are graded (A) in relation to their visual appearance passing successfully as shown in Table 6, where the formula (LM2) containing maline as oil phase tween 80 as surfactant and propylene glycol as a co-surfactant achieved the lowest time of emulsification in comparsion to conventional liquid SEDD (LT1 and LT2) attributing to the ability in reducing the interfacial tension and thus excess diffusion of the aqueous phase into the oil occurs, causing interfacial disruption and discharge of droplets into the bulk aqueous phase. Similar results was observed with Candesartan cilexetil prepared as liquid SEDDs [33].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…All the prepared liquid SEDD formulas are graded (A) in relation to their visual appearance passing successfully as shown in Table 6, where the formula (LM2) containing maline as oil phase tween 80 as surfactant and propylene glycol as a co-surfactant achieved the lowest time of emulsification in comparsion to conventional liquid SEDD (LT1 and LT2) attributing to the ability in reducing the interfacial tension and thus excess diffusion of the aqueous phase into the oil occurs, causing interfacial disruption and discharge of droplets into the bulk aqueous phase. Similar results was observed with Candesartan cilexetil prepared as liquid SEDDs [33].…”
Section: Resultssupporting
confidence: 86%
“…A value closer to 100% indicated the formulations' transparency and stability, indicating a high surface area for drug release [35]. The droplet size is a crucial factor in the self-emulsification performance of the emulsion as it determines the rate and extent of drug release as well as drug absorption [33]. It was noticed from the results (table 8) that the relative proportion of surfactant to co-surfactant has variable effects on the droplet size.…”
Section: Resultsmentioning
confidence: 98%
“…Measurement of the Globules Size, Zeta potential, and Polydispersity Index(PDI) Globule size of nanoemulsion affects strongly the rate and extent of drug release from formulas, also the stability of emulsion is affected by globule size, zeta potential and polydispersity index. PDI describe the ratio of standard deviation to particle size average, a low PDI means narrow droplet size distribution, indicating homogeneity, uniformity of size distribution, and stability upon storage for long time (35). From results in table (2) ,it's obvious that all formulas has a uniform globular size.…”
Section: Preparation Of Ticagrelor Liquid Self-nanoemulsion Formulasmentioning
confidence: 98%
“…Thus, ZP could relate to colloidal dispersion stability through resisting aggregation and coalescence in GIT environment or during storage time (38) . Hernández and Goymann reported that ZP values above 8-9 mV are required for nanoparticle stability (39) . In general, formulations having ZP value higher than + 30 mV or lower than -30 mV are regarded as absolutely electrically stable (38) .…”
Section: Measurement Of the Globules Size Polydispersity Index (Pdi) ...mentioning
confidence: 99%